Odpowiedzi

2009-12-14T20:08:54+01:00
A) x+y=2
x-y=1
------------
2x= 2+1
2x=3 // 2
x = 3/2

x=3/2
3/2 +y = 2
y= 2-3/2
y = - 1/2

b)2x+y=5
4x-y=10
------------
6x = 15 //6
x = 15/6
x= 5/2

x=5/2
2* 5/2 +y = 5
5 + y = 5
y= 5-5
y = 0

c)3x+2y=2 /* -1
3x+y=1,5

-3x- 2y= -2
3x + y = 1,5
-----------------
-y = -0,5 // -1
y = 0,5

3x + 0,5 = 1,5
3x + 1,5 - 0,5
3x = 1 // 3
x = 1/3

d)x+y=0 /* -2
2x+4y=1

-2x - 2y = 0
2x + 4y = 1
----------------
-2x = 1 // -2
x = -1/2

-1/2 + y = 0
y= 0 + 1/2
y = 1/2

e)3x-2y=3 /* -1
3x+y=1,5

-3x +2y = -3
3x +y = 1,5
----------------
3y = -1,5 //3
y = 0,5

3x - 2 * 0,5 = 3
3x = 3 + 1
3x= 4 //3
x= 4/3

;)
2009-12-14T20:13:09+01:00
A) x+y=2
x-y=1

y=2-x
x=1+y

y=2-x
x=1+2-x

y=2-x
2x=3 |:2

y=2-x
x=2/3

y=2-2/3
x=2/3

y=1/3
x=2/3

b)2x+y=5
4x-y=10

2x=5-y
-y=10+4x

2x=5-y
y=-10-4x

2x=5+10-4x
y=-10-4x

6x=15 |:6
y=-10-4x

x=1/2
y=-10-2

x=1/2
y=8

c)
3x+2y=2
3x+y=1,5

3x=2-2y
y=1,5-3x

3x=2-2*(1,5-3x)
y=1,5-3x

3x=2-3-6x
y=1,5-3x

9x=1 |:9
y=1,5-3x

x=1/9
y=1,5-3*1/9

x=1/9
y=1,5-1/3

x=1/9
y=0,16
tego przykładu nie jestem pewna

d)x+y=0
2x+4y=1

x=-y
-2y+4y=1

x=-y
2y=1 |:2

x=-y
y=1/2

e)3x-2y=3
3x+y=1,5

3x=3-2y
y=1,5-3x

3x=3-2*(1,5-3x)
y=1,5-3x

3x=3-3-9x
y=1,5-3x

12x=0 |:12
y=1,5-3x

x=0
y=1,5